2023
DOI: 10.1186/s13046-022-02574-0
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of PKM2-dependent glycolytic and non-glycolytic pathways by ENO2 in head and neck cancer development

Abstract: Background Enolase 2 (ENO2) is a crucial glycolytic enzyme in cancer metabolic process and acts as a “moonlighting” protein to play various functions in diverse cellular processes unrelated to glycolysis. ENO2 is highly expressed in head and neck squamous cell carcinoma (HNSCC) tissues relative to normal tissues; however, its impact and underlying regulatory mechanisms in HNSCC malignancy remain unclear. Methods Molecular alterations were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…We hypothesized that the ENO2-mediated glycolysis process might play a crucial role in supplying energy for anoikis resistance in ATC cells. Previous studies have shown that ENO2 is significantly involved in the development of various tumors ( 22 , 28 , 53 ), prompting our assumption that regulating ENO2 expression might influence the fate of cells under detached culture conditions. Our in vitro experiments demonstrated that the knockdown of ENO2 significantly increased cell apoptosis in the SW1736 and 8305C cells, coupled with a significant decrease in sphere formation.…”
Section: Discussionmentioning
confidence: 93%
“…We hypothesized that the ENO2-mediated glycolysis process might play a crucial role in supplying energy for anoikis resistance in ATC cells. Previous studies have shown that ENO2 is significantly involved in the development of various tumors ( 22 , 28 , 53 ), prompting our assumption that regulating ENO2 expression might influence the fate of cells under detached culture conditions. Our in vitro experiments demonstrated that the knockdown of ENO2 significantly increased cell apoptosis in the SW1736 and 8305C cells, coupled with a significant decrease in sphere formation.…”
Section: Discussionmentioning
confidence: 93%
“…PKM2 is highly expressed in cancer cells and plays a critical role in promoting cell proliferation and survival. Recent studies have shown that PKM2 expression and activity are regulated by various signaling pathways, including oncogenic signaling pathways and metabolic stress pathways ( 29 , 30 ). In addition, PKM2 has been found to interact with other proteins involved in cell signaling and metabolism, such as HSP90 and hypoxia-inducible factor–1α, which can influence its activity and function ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The full-length Flag-tagged human HSP90AA1 was cloned into lentiviral pCDH-CMV-MCS-EF1-Puro (System Biosciences, Mountain View, CA) vector as previously described ( 7 ). The full-length HA-tagged human PKM gene was cloned into the pDONR-221 lentiviral expression vector (Invitrogen) as we previously described ( 29 ). pcDNA3.1-PFKP containing human PFKP gene was provided by Z. Lu ( 44 ).…”
Section: Methodsmentioning
confidence: 99%
“…COL1A1 is the main constituent of type I collagen, and abnormal COL1A1 expression is associated with many cancers [ 39 41 ]. ENO2 (enolase 2) is a critical glycolytic enzyme in cancer metabolic processes [ 42 ]. Recent investigations have discovered that the overexpression of ENO2 encourages cell proliferation and glycolytic enrichment in papillary RCC [ 43 ].…”
Section: Discussionmentioning
confidence: 99%